Hypoxia-induced autophagy drives colorectal cancer initiation and progression by activating the PRKC/PKC-EZR (ezrin) pathway. Issue 8 (2nd August 2020) - Qureshi-Baig, Komal; Kuhn, Diana; Viry, Elodie; Pozdeev, Vitaly I.; Schmitz, Martine; Rodriguez, Fabien; Ullmann, Pit; Koncina, Eric; Nurmik, Martin; Frasquilho, Sonia; Nazarov, Petr V.; Zuegel, Nikolaus; et al.
ABSTRACT: In solid tumors, cancer stem cells (CSCs) or tumor-initiating cells (TICs) are often found in hypoxic niches. Nevertheless, the influence of hypoxia on TICs is poorly understood. Using previously established, TIC-enrichedpatient-derived colorectal cancer (CRC) cultures, we show that hypoxia increases the self-renewal capacity of TICs while inducing proliferation arrest in their more differentiated counterpart cultures. Gene expression data revealed macroautophagy/autophagy as one of the major pathways induced by hypoxia in TICs. Interestingly, hypoxia-induced autophagy was found to induce phosphorylation of EZR (ezrin) at Thr567 residue, which could be reversed by knocking down ATG5, BNIP3, BNIP3L, or BECN1 . Furthermore, we identified PRKCA/PKCα as a potential kinase involved in hypoxia-induced autophagy-mediated TIC self-renewal. Genetic targeting of autophagy or pharmacological inhibition of PRKC/PKC and EZR resulted in decreased tumor-initiating potential of TICs. In addition, we observed significantly reduced in vivo tumor initiation and growth after a stable knockdown of ATG5 . Analysis of human CRC samples showed that p-EZR is often present in TICs located in the hypoxic and autophagic regions of the tumor. Altogether, our results establish the hypoxia-autophagy-PKC-EZR signaling axis as a novel regulatory mechanism of TIC self-renewal and CRC progression. Autophagy inhibition might thus represent a promising therapeutic strategy for cancer patients. Abbreviations: ATG: autophagy related; BECN1: beclin 1; BNIP3: BCL2 interacting protein 3; BNIP3L: BCL2 interacting protein 3 like; CQ: chloroquine; CSC: cancer stem cells; CRC: colorectal cancer; HIF1A/HIF-1α: hypoxia inducible factor 1 subunit alpha; MAP1LC3/LC3: microtubule associated protein 1 light chain 3; PRKC/PKC: protein kinase C; SQSTM1/p62: sequestosome 1; TICs: tumor-initiating cells.